Serum anti-Müllerian hormone as a predictor of metaphase II oocyte yield during controlled ovarian stimulation (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: The potential to predict metaphase II (MII) oocyte yield in controlled ovarian stimulation (COS) has not been elucidated, despite being a mandatory predictor of fertilization potential. Hence this area is marred by the diversity of approaches to ovarian stimulation and the deficiency of standards.Objective: To determine the role of serum anti-Müllerian hormone (AMH) as a predictor of MII oocyte yield during controlled ovarian stimulation at a private fertility clinic in Nairobi.Methods: A retrospective descriptive cohort study design was employed in which MII outcomes during COS were compared among women aged 18-45 years with normal or low serum AMH levels. Data were collected sequentially until the desired sample size was achieved. Data were analyzed using the IBM statistical package for social sciences (SPSS) version 24.0 and STATA version 15. The level of significance was set at p